Diagnosis of SARS-CoV-2: Experience with rapid immunochromatography tests and RT‒qPCR - David Alejandro Cabrera Gaytán; Porfirio Felipe Hernández Bautista; Clara Esperanza Santacruz Tinoco; Julio Elias Alvarado Yaah; Yu-Mei Anguiano Hernández; Bernardo Martínez Miguel; Alfonso Vallejos Parás; Lumumba Arriaga Nieto; Nancy Sandoval Gutiérrez; Concepción Grajales Muñiz; Alejandro Moctezuma Paz; Leticia Jaimes Betancourt (Journal of Clinical Virology Plus)
Background: Mexico has experienced six waves were experiences between 2019 and 2023 of coronavirus disease 2019 (COVID-19). In the first wave, diagnosis relied on RT‒qPCR; rapid tests for SARS‒CoV‒2 were introduced from the second wave onward. However, the patterns of results with this test in Mexico have not been documented in population-based studies. Objective: To describe the temporal patterns of the results from RT-qPCR and rapid immunochromatography tests for SARS-CoV-2 detection from the second to the sixth epidemic wave in Mexico. Materials and methods: This was a multicenter study at the national level. The operational definition of suspected cases of viral respiratory illness, confirmed cases of SARS-CoV-2 in Mexico, and data for asymptomatic individuals who required rapid testing between 2020 and 2023 were employed; testing was employed for the entirety of the four years. Positivity was estimated per epidemiological week, state, and condition for both tests. Spearman's correlation coefficient, trend chi-square analysis, and odds ratios with 95 % confidence intervals were used. Results: A total of 1749,765 cases had RT‒qPCR data recorded from 2020 to 2023, and 8356,903 cases with rapid tests were conducted for virus identification. Compared with the rest of the country, the southeastern region exhibited different patterns. The positivity rate of rapid tests from the epidemiological surveillance system was lower than that of RT‒qPCR during interepidemics periods, whereas the positivity rate of rapid tests for symptomatic individuals was higher than that of RT‒qPCR tests over two years. Conclusion: Rapid tests for SARS-CoV-2 identification in Mexico were affordable and timely at the local level. These tests revealed differing epidemic wave patterns in the southeastern region of the country.